Genetic Testing for Huntington’s Disease in Parkinsonism - Rahman, MS; Nagai, Y; Popiel, HA; Fujikake, N; Okamoto, Y; Ahmed, MU; Islam, MA; Islam, MT; Ahmed, S; Rahman, KM; et al. (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):510-4 The abstract of this article is available on the PubMed website